Immediate effect of ACL kinesio taping technique on knee joint biomechanics during a drop vertical jump: a randomized crossover controlled trial - Weerawat Limroongreungrat; Chuanpis Boonkerd (BMC, 2019)
Abstract Background The purpose of this study was to investigate the effect of an ACL Kinesio Taping technique (ACL-KT) on knee joint biomechanics during a drop vertical jump (DVJ). Methods Twenty healthy male participants (age 21.1±0.3 years; mass 64.2±4.3 kg; height 174.2±5.5 cm) participated in this study. The participants performed a DVJ and landed onto 2 adjacent force platforms under both ACL-KT and placebo (PT) conditions. All data were collected with 3-D motion analysis and comparison peak knee joint angles and moments, and knee joint angle at initial contact (IC) between conditions analyzed using a paired sample t-test. Statistical parametric mapping (SPM) was selected to assess difference between groups for the entire three-component knee trajectory during the contact phase. Results ACL-KT had a significant effect on decreasing knee abduction angle at IC (1.43±2.12 deg.) compared with the PT (−1.24±2.42 deg.) (p=0.04). A significant difference in knee abduction angle between the taping conditions was found between 100 ms before IC, at IC and 100 ms after IC (p<0.05). There were no significant differences (p>0.05) found between conditions in any of the other variables. Conclusion This result confirmed that the application of ACL-KT is useful to reduce knee abduction angle at IC during a DVJ in healthy participants. Therefore, ACL-KT may be an acceptable intervention to reduce ACL injury risk. Trial registration Retrospective registered on 25 September 2018. Trial number: TCTR20180926005